Da Baloṡi zhabay nūmyālī inqilābī shāʻir, Mīr Gul Khān Naṣīr - Baloṡ, ʻAbd al-Raḥmān (da Afghānistān da ʻUlūmo Akāḍemī, da Zhabo aw Adabiyāto Instītūt, 1979)
On the life and works of Gul Khan Nasir, b. 1914, eminent Balochi poet; includes his selected poems in Balochi.